Animal Knowledge Application with Augmented Reality Technology - Kumajas, Sondy (JR Education, 2025)
The Animal Knowledge Application with Augmented Reality Technology is a learning support application on the theme of animals for early childhood. This application utilizes augmented reality technology, which displays a real environment combined with three-dimensional or two-dimensional virtual objects that are displayed in real-time. This research aims to build an Animal Knowledge Application with Augmented Reality Technology. This Animal Knowledge Application with Augmented Reality Technology uses the MDLC (Multimedia Development Life Cycle) method. The results of this study include animal recognition applications utilizing 3D objects, which employ mobile-based Augmented Reality technology on the Android operating system. These applications can display 3D animal objects, accompanied by audio explanations. Based on the results of application functionality testing, each function in the application runs according to the expected results. Application testing is also carried out on several devices, and the result of the test is that the application on the smartphone being tested can run smoothly according to features, and the appearance of the application adjusts to the resolution of every smartphone.